IMplementation of Realist Findings to Create an Innovative Pathway for Weight Gain Associated With Anti-Psychotic Use in Patients Living With Severe MENTal Illness (SMI) – IMPLeMENT - Jasleen Deol; Hafsah Habib; Ian Maidment; Ita Fitzgerald; Jo Howe (BJPsych Open, 2025)
Aims: Antipsychotic medications are essential in treating patients with severe mental illness (SMI), but they are associated with rapid weight gain, significantly increasing the risk of cardiovascular disease and diabetes. These physical health complications contribute to reduced life-expectancy and development of preventable physical health conditions. The NIHR-RESOLVE study (REF:HSDR131871) explored non-pharmacological interventions for antipsychotic induced weight gain, and highlighted the urgent need for a structured, preventative pathway to support patients at risk.